1997
DOI: 10.1038/ki.1997.96
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of angiotensin II on the plasminogen/plasmin system in rat mesangial cells

Abstract: Previous studies indicate that angiotensin II (Ang II) stimulates extracellular matrix synthesis through induction of transforming growth factor-beta (TGF-beta) expression. Here we investigate Ang II effects on the plasmin protease system. Plasmin both degrades extracellular matrix itself and activates metalloproteinases which then degrade collagens. Plasmin production is determined by the balance between plasminogen activators (PA) and their inhibitors (PAI-1,2). The data presented here indicate that Ang II t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…These clinical and experimental in vivo studies have strongly suggested that the renoprotective effect of these antihypertensive agents results from not simply the inhibition of its hemodynamic action but also blockade of its hemodynamicindependent actions. In fact, many studies, including our previous in vitro studies, have disclosed the mechanisms and the role of Ang II-induced ECM deposition through mesangial cells (11)(12)(13). Ang II stimulates ECM synthesis through the induction of TGF-␤1 expression in cultured rat glomerular mesangial cells (11) and affects the plasminogen activator/ plasminogen activator inhibitor-1 system to result in accelerated deposition of ECM (12), which constitutes evidence that Ang II can act as a potent fibrotic molecule independent of its effects on BP.…”
mentioning
confidence: 99%
“…These clinical and experimental in vivo studies have strongly suggested that the renoprotective effect of these antihypertensive agents results from not simply the inhibition of its hemodynamic action but also blockade of its hemodynamicindependent actions. In fact, many studies, including our previous in vitro studies, have disclosed the mechanisms and the role of Ang II-induced ECM deposition through mesangial cells (11)(12)(13). Ang II stimulates ECM synthesis through the induction of TGF-␤1 expression in cultured rat glomerular mesangial cells (11) and affects the plasminogen activator/ plasminogen activator inhibitor-1 system to result in accelerated deposition of ECM (12), which constitutes evidence that Ang II can act as a potent fibrotic molecule independent of its effects on BP.…”
mentioning
confidence: 99%
“…Ang II induced the synthesis and secretion of FN, and of type I and III collagen from MC (7,8,12). In our previous study, Ang II was dramatically increased in the local renal tissue of puromycin nephropathy rats, and this increase was related with the progression of puromycin nephropathy.…”
Section: Discussionmentioning
confidence: 97%
“…Both Ang II (or its hexapeptide metabolite, Ang IV) and aldosterone increase PAI-1 expression in a variety of cell types, including astrocytes, 35 endothelial cells, 4 vascular smooth muscle cells, 36 proximal tubular epithelial cells, 37 and mesangial cells. 38 Systemic infusion of Ang II increases vascular, renal, and hepatic PAI-1 expression in rats, 39 whereas treatment of animals with ACE inhibitors, AT 1 receptor antagonists, or aldosterone receptor antagonists decreases tissue PAI-1 expression. 15,40 Ang II stimulates PAI-1 expression through a serum-inducible element localized to a sequence between Ϫ47 and Ϫ38 bp in the PAI-1 promoter.…”
Section: Discussionmentioning
confidence: 99%